NKG2D Enhances Double-Negative T Cell Regulation of B Cells - Hu, Shi-hua; Zhang, Long-hui; Gao, Jie; Guo, Jing-heng; Xun, Xiao-dong; Xiang, Xiao; Cheng, Qian; Li, Zhao; Zhu, Ji-ye (Frontiers in Immunology, 2021)
Numerous studies have reported that there is a small subpopulation of TCRαβ+CD4-CD8- (double-negative) T cells that have regulatory functions in the peripheral lymphocyte population. However, the origin of these double-negative T (DNT) cells is still debated. Some researchers have reported that DNT cells originate from the thymus, while others have argued that they are derived from peripheral immune induction. Here, we report a possible mechanism by which nonregulatory CD4+ T cells can be induced to become regulatory double-negative T (iDNT) cells in vitro. We found that immature bone marrow dendritic cells (CD86+MHC-II- DCs) rather than mature DCs (CD86+MHC-II+) induced high levels of iDNT cells. Adding an anti-MHC-II antibody to the CD86+MHC-II+ DC group significantly increased induction. These iDNT cells could promote B cell apoptosis and inhibit B cell proliferation and plasma cell formation. Moreover, a group of iDNT cells was found to express NKG2D. Compared with NKG2D- iDNT cells, NKG2D+ iDNT cells could release more granzyme B to enhance B cell regulation. This enhancement might function through NKG2D ligands expressed on B cells upon lipopolysaccharide stimulation. These results demonstrate that MHC-II impedes induction and that iDNT cells may be MHC independent. NKG2D expressed on iDNT cells enhances the regulatory function of these cells. Thus, our findings aim to elucidate one of the possible mechanisms of induction of peripheral immune tolerance and to provide a potential treatment for chronic allograft rejection in the future.